Romance during the Revolution In Surabaya and Its Surrounding Areas - Kasuma, Gayung (Universitas Airlangga, 2024)
This article discusses the romantic aspects of social life during revolutionary period in the city of Surabaya and its surroundings. After the battle of November 1945, the term